2010
DOI: 10.1159/000272953
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time RT-PCR Analysis for Evaluating the Her2/neu Status in Breast Cancer

Abstract: Objective: The Her2/neu status is of great clinical value in breast tumor patients. Fluorescence in situ hybridization (FISH) and immunohistochemistry (IHC) techniques are the test of choice for many practicing pathologies. The main objective of this retrospective study was to investigate the relationship between Her2/neu breast cancer amplification and overexpression (DNA, mRNA and protein). Methods: To accomplish this goal, we evaluated Her2/neu mRNA expression by real-time quantitative RT-PCR, gene amplific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 56 publications
3
15
1
Order By: Relevance
“…This might be due to the differences in the categorization of breast tumor samples of the different studies and the variability of gains of region 17q12–21. In this study, the evaluation of HER2 mRNA expression levels showed a statistically significant correlation with DNA amplification, confirming the trend observed in our previous report [35]. However, qRT-PCR is an extremely sensitive and specific technique and there is also substantial scientific documentation supporting the variability of HER2 mRNA analysis among IHC and FISH categories [36,37,38].…”
Section: Discussionsupporting
confidence: 90%
“…This might be due to the differences in the categorization of breast tumor samples of the different studies and the variability of gains of region 17q12–21. In this study, the evaluation of HER2 mRNA expression levels showed a statistically significant correlation with DNA amplification, confirming the trend observed in our previous report [35]. However, qRT-PCR is an extremely sensitive and specific technique and there is also substantial scientific documentation supporting the variability of HER2 mRNA analysis among IHC and FISH categories [36,37,38].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study reported no differences in the HER2 mRNA levels between adenomas and carcinomas or between presence and absence of lymph node involvement of cMTs [23]. In human breast cancer, reports on the interaction between mRNA expression and HER2 protein or DNA amplification levels did not reach agreement [5,13]. Since there was no significant difference in HER2 expression among cMT tissue samples in the present study, HER2 was not assessed in FNB samples.…”
Section: Discussioncontrasting
confidence: 68%
“…In addition, increased CEP17 copy number is frequently found in tumors showing HER2 overexpression, including those with a borderline (2þ) score, as confirmed in our study. [18][19][20] Our series included unselected (no prior IHC determination of HER-2/neu protein) and selected (equivocal IHC staining results) cases, reflecting our referral laboratory's mixture of cases received from different institutions.…”
mentioning
confidence: 99%